Analisis Kekuatan Tali Baja Pada Lift Schindler Kapasitas 1600 Kg - Ahmad Zayadi; Cahyono Her Prasetyo (FTK UNSURYA, 2020)
Steel rope is one of the most important parts of the aircraft's systems lifter. Strength steel cord vary, depending on the terms of usage and requirements of a building. Construction steel rope which is typical for elevator consists of 8-spun wound together, the direction to the left or right with the middle core. Each spun steel strap consists of 19 wires is 9.9.1, which means outside the wire 9, 9 inside and one in the center. Sectional area of the steel rope (F152) based on the tensile stress to a steel rope (S) is 1.9 cm. Tensile stress occurs in the steel cord is equal to (S) = 1894 kg. While the tensile stress is permitted (Smax) = 2800 kg. Actual breaking strength steel strap (P) by the safety factor with the types of mechanisms and operating conditions (K) is (P) = 10417 kg. The lifetime of steel ropes obtained from this analysis is 120 months or 10 years in normal use 8 hours per day. Steel rope used types : 8 x 19 = 152 + 1 Fiber Core specification: diameter steel rope (d): 10 mm, weight of the rope (W): 1.15 kg / m, the burden of broken steel rope (Pb): 15,400 kg, rope fracture stress (σb): 140-159 kg / mm². Due to the tensile stress (ST) = 1894 kg less than the tensile stress that is authorized (Smax) = 2800 kg, it can be concluded that the steel straps secure against tensile loads that occur